Principles of nature in product design - Trautmann, Laura (Design of Machines and Structures, 2021)
Product designers should pay attention to many attributes of a product during design, however, studies have shown that besides the functionality, the aesthetically-pleasing appearance of products attracts consumers, and it has a significant effect on the buying process. Thus, it is efficient to know what geometries, colours, materials, etc., are pleasing to the human eye. This article deals with geometries that appear in nature since these forms are pleasing to many people of different generations and cultures and provide a sense of harmony. The hypothesis is that the usage of the mathematically describable principles of nature – such as Fractals, Golden Ratio, Fibonacci Sequence, Voronoi Diagram – could result in a betterlooking design that increases the success of the product, like in the cases of Stradivarius violin, Aston Martin, or Apple logo.